2013
DOI: 10.2217/cpr.12.73
|View full text |Cite
|
Sign up to set email alerts
|

The online issue: treating problem gambling in an era of uncontrolled access

Abstract: The findings of this study need replication in larger samples and on a wider severity scale. Nevertheless, the heterogeneity of patients with FEP might impact on treatment. Policymakers should recognize the importance of the diagnostic and outcome assessment in the treatment of severe mental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…[12][13][14][15][16][17][18][19] This also renders the potential for providers to monitor, and track and control behaviors in an online environment. 15,20,21 Indeed, Auer and Griffiths 12 showed that behavioral tracking systems that allowed players to set voluntary limits could benefit the most gaming intense consumers.…”
Section: Consumer Trackingmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19] This also renders the potential for providers to monitor, and track and control behaviors in an online environment. 15,20,21 Indeed, Auer and Griffiths 12 showed that behavioral tracking systems that allowed players to set voluntary limits could benefit the most gaming intense consumers.…”
Section: Consumer Trackingmentioning
confidence: 99%